2016
DOI: 10.4103/1658-354x.179121
|View full text |Cite
|
Sign up to set email alerts
|

Is it safe to use frova airway intubating device during tracheal intubation in difficult airway patient with multiple and chest trauma?

Abstract: Traumatic chest injury is one of the leading causes of death in motor vehicle accident (MVA). A complete tracheobronchial injury occurred in 1% of trauma cases and most of the cases died before arrival to the emergency department. We report a 37-year-old female involved in MVA presented to the emergency room (ER) with normal vital signs. Ten minutes later, her saturation dropped to 75%, which required ventilation; however, two attempts for endotracheal intubation failed. The third time frova airway intubating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…477 Case reports observed intubation successes with bougies, introducers, and stylets for patients with unanticipated or emergency difficult airways (Category B4-B evidence). 114,[478][479][480][481][482][483][484][485] Nonrandomized studies comparing videolaryngoscopes with direct laryngoscopy reported equivocal findings for intubation success with difficult airways in emergency departments (Category B1-E evidence). 6,486,487 Observational studies indicated successful videolaryngoscope-guided intubation rates after failed intubation ranging from 92 to 100% for unanticipated and emergency difficult airways (Category B4-B evidence).…”
Section: Recommendations For Anticipated Difficult Airway Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…477 Case reports observed intubation successes with bougies, introducers, and stylets for patients with unanticipated or emergency difficult airways (Category B4-B evidence). 114,[478][479][480][481][482][483][484][485] Nonrandomized studies comparing videolaryngoscopes with direct laryngoscopy reported equivocal findings for intubation success with difficult airways in emergency departments (Category B1-E evidence). 6,486,487 Observational studies indicated successful videolaryngoscope-guided intubation rates after failed intubation ranging from 92 to 100% for unanticipated and emergency difficult airways (Category B4-B evidence).…”
Section: Recommendations For Anticipated Difficult Airway Managementmentioning
confidence: 99%
“…477 Case reports observed intubation successes with bougies, introducers, and stylets for patients with unanticipated or emergency difficult airways (Category B4-B evidence ). 114,478–485…”
Section: Unanticipated and Emergency Difficult Airway Managementmentioning
confidence: 99%
“…Moreover, difficult airway in GA is not common, but could inevitably increase the endotracheal intubation time. [ 14 , 15 ] After termination of operation under GA, the anesthetic drugs were discontinued, and neuromuscular blockade was reversed by using neostigmine and atropine. Recovery of consciousness occurred when the concentration of anesthetics in the brain dropped below a certain level.…”
Section: Discussionmentioning
confidence: 99%
“…Abzuwägen ist hierbei allerdings auch der potenzielle Schaden, der durch die Nutzung eines Guides bei eingeschränkter Sicht entstehen und ein vorhandenes Trauma vergrößern kann. In der Literatur sind verschiedene Komplikationen bei Traumapatienten wie Blutung oder Schädigungen der Atemwege benannt, sodass der Einsatz kritisch hinterfragt werden muss [8]. Nachdem der Bronchusabriss in der Klinik bekannt war, wäre auch ein Vorschieben des liegenden Tubus in den linken Hauptbronchus unter Bronchoskopie zu erwägen gewesen [9].…”
Section: Introductionunclassified